Postoperative Complications after Thoracic Surgery in the Morbidly Obese Patient. (12th December 2011) - Cooper, Lebron
Abstract : Little has been recently published about specific postoperative complications following thoracic surgery in the morbidly obese patient. Greater numbers of patients who are obese, morbidly obese, or supermorbidly obese are undergoing surgical procedures. Postoperative complications after thoracic surgery in these patients that can lead to increased morbidity and mortality, prolonged hospital stay, and increased cost of care are considered. Complications include difficulties with mask ventilation and securing the airway, obstructive sleep apnea with risk of oversedation, pulmonary complications related to reduced total lung capacity, reduced functional residual capacity, and reduced vital capacity, risks of aspiration pneumonitis and ventilator-associated pneumonia, cardiomyopathies, and atrial fibrillation, inadequate diabetes management, positioning injuries, increased risk of venous thrombosis, and pulmonary embolism. The type of thoracic surgical procedure may also pose other problems to consider during the postoperative period. Obese patients undergoing thoracic surgery pose a challenge to those caring for them. Those working with these patients must understand how to recognize, prevent, and manage these postoperative complications.